The application of the Planning Indicators Model as a tool for measuring the success of the Metropolitan Spatial Development Framework in the Cape Metropolitan Area - Letsie, Moipone (Moipone Amelia Mantsebo) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA)--University of Stellenbosch, 2004.